Identification of Tick Ixodes ricinus Midgut Genes Differentially Expressed During the Transmission of Borrelia afzelii Spirochetes Using a Transcriptomic Approach - Mahmood, Sazzad; Sima, Radek; Urbanova, Veronika; Trentelman, Jos J. A.; Krezdorn, Nicolas; Winter, Peter; Kopacek, Petr; Hovius, Joppe W.; Hajdusek, Ondrej (Frontiers in Immunology, 2021)
Lyme borreliosis is an emerging tick-borne disease caused by spirochetes Borrelia burgdorferi sensu lato. In Europe, Lyme borreliosis is predominantly caused by B. afzelii and transmitted by Ixodes ricinus. Although Borrelia behavior throughout tick development is quite well documented, specific molecular interactions between Borrelia and the tick have not been satisfactorily examined. Here, we present the first transcriptomic study focused on the expression of tick midgut genes regulated by Borrelia. By using Massive Analysis of cDNA Ends (MACE), we searched for tick transcripts expressed differentially in the midgut of unfed, 24 hours-fed, and fully-fed I. ricinus nymphs infected with B. afzelii. In total, we identified 553 upregulated and 530 downregulated tick genes and demonstrated that B. afzelii interacts intensively with the tick. Technical and biological validations confirmed the accuracy of the transcriptome. The expression of five validated tick genes was silenced by RNA interference. Silencing of the Uncharacterized protein (GXP_Contig_30818) delayed the infection progress and decreased infection prevalence in the target mice tissues. Silencing of other genes did not significantly affect tick feeding nor the transmission of B. afzelii, suggesting a possible role of these genes rather in Borrelia acquisition or persistence in ticks. Identification of genes and proteins exploited by Borrelia during transmission and establishment in a tick could help the development of novel preventive strategies for Lyme borreliosis.